Effectiveness of E-Module to Improve Students' Critical Thinking Skills in High School Science Learning: Literature Study - Diniyatushoaliha, Ainun (International Journal of Science Education and Science, 2024)
This literature review article (literature study) aims to identify the effectiveness of e-modules in improving students' critical thinking skills in high school science learning (Biology, Physics, Chemistry). A literature study was carried out to find and understand articles discussing the effectiveness of e-modules and critical thinking skills in high school science learning. The research results show that the Android-based Selvo E-Module (Volta Cell) and the HOTS-based physics e-module are effective in improving students' critical thinking skills in high school science learning with an increase in test results in the 61-65 range.